1997
DOI: 10.1271/bbb.61.1772
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Activity of Water Extracts ofLagerstroemia speciosaLeaves

Abstract: In order to develop naturally occurring antioxidants from edible plants, the antioxidative effect of hot water extracts of Lagerstroemia speciosa leaves, known by the Tagalog name of banaba in the Phillipines, was studied. The content of tannin in banaba extract was 36.8% in dry weight. Banaba extract showed strong antioxidative activity in a linoleic acid autoxidation system. Banaba extract was found to have a potent radical scavenging action on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals and superoxide rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…The results of this study thus strongly suggested that extract has an anti-oxidant property. This is consistent with the results published by Unno et al, 1997. The antidiabetic and the antioxidant properties of the extract might be acting in a synergistic fashion.…”
Section: Resultssupporting
confidence: 93%
“…The results of this study thus strongly suggested that extract has an anti-oxidant property. This is consistent with the results published by Unno et al, 1997. The antidiabetic and the antioxidant properties of the extract might be acting in a synergistic fashion.…”
Section: Resultssupporting
confidence: 93%
“…However, the people of South-east Asia used the leaves of L. speciosa for the treatment of diabetes mellitus and obesity [2]. The aqueous extract of leaves of L. speciosa leaves possess potent antioxidant and free radical scavenging activities by scavenging 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) and superoxide radical as well as inhibiting lipid peroxidation [3]. Moreover, the bioactive phytochemicals isolated from different parts of L. speciosa , have revealed hypoglycemic, antibacterial, anti-inflammatory, antioxidant and hepato protective properties [4–9].…”
Section: Introductionmentioning
confidence: 99%
“…Interest is increasing in the protective biological effects of some natural antioxidants, especially from edible plants, which are candidates for preventing various inflammatory disorders and extending the life span of humans (Unno et al 1997;Yang et. al 1998;Virgili et al 1998;Wakabayashi 1999).…”
Section: Discussionmentioning
confidence: 99%